Improving maternal hemoglobin: comparing the effectiveness of dates and mung bean cookies in anemia pregnant women - Yunia, Dela; Diana, Helmi; Purnamasari, Wiwin Mintarsih (Jurnal Kesehatan Ibu dan Anak, 2024)
Anemia remains a significant health issue among pregnant women in Indonesia, with prevalence rates reaching 50–63%. In addition to iron supplementation, food-based micronutrient interventions such as date fruit and mung bean cookies may help improve hemoglobin levels. However, limited studies have compared the effectiveness of these two food sources. This study aimed to compare the effects of date fruit and mung bean cookies on hemoglobin levels in pregnant women with anemia. A quasi-experimental study with a two-group pre-test-post-test design was conducted at Bojongasih Public Health Center, Tasikmalaya, Indonesia in 2024. A total of 34 pregnant women with anemia were recruited using total sampling and divided into two groups: date fruit (n = 17) and mung bean cookies (n = 17). Hemoglobin levels were measured before and after 14 days of intervention. Paired t-tests were used for statistical analysis. The date group showed a greater mean increase in hemoglobin levels (from 9.906 to 10.871 g/dL; increase of 0.965) compared to the mung bean cookie group (from 9.888 to 10.476 g/dL; increase of 0.588). The difference was statistically significant (p = 0.001). Date fruit was more effective than mung bean cookies in increasing hemoglobin levels among pregnant women with anemia. These findings suggest that date fruit can be considered as a complementary nutritional strategy to support iron supplementation during pregnancy.